Dinâmica de inovação e desenvolvimento regional: uma análise da região metropolitana de Campina Grande - PB - Maciel, Dayanna dos Santos Costa (2019)
The present study explores the relationship among innovation and regional development based on the perception of the sources involved in the dynamics of innovation established in a certain territory. For this purpose, based on the innovation dynamics established in the metropolitan region of Campina Grande, this model takes as its theoretical model the triple helix model (ETZKOWITZ, 2008) and conceives as a dynamic of innovation the set of interactions, articulations, relationships and networks cooperation among actors, sources or sectors involved in promoting innovation in this region. In this context, this study aims to analyze the dynamics of innovation, based on the triple helix, and its contributions to the development of the metropolitan region of Campina Grande - Paraiba from the perspective of the main institutional sectors involved. In order to meet this proposal, an exploratory and descriptive research was carried out, using a mixed methodological approach (qualitative and quantitative) through the collection and analysis of primary and secondary data. For the collection of data in secondary sources we used documentary research and as analysis technique, content analysis. To the collection of primary data, was used as a collection tool a questionnaire composed of open and closed questions, and as analysis techniques, content analysis and descriptive statistics. At the end of the research it is concluded that the innovation dynamics established in the studied region is fostered by a triple helix on a third stage of development with intense interaction relations among the institutional sectors and agents that compose it (academy, state and industry) however, this dynamics contributes little to the development of the researched region, since negative observations regarding this contribution is verified throughout the research, such as the lack of alignment of the innovations and contributions of this dynamic with the needs and problems of the region.